Komunikasi Dialektik Dalam Relasi Hindu Dan Islam Di Bali - I Nyoman Yoga Segara (Jayapangus Press, 2020)
This article on Hindu and Islamic relations is the result of research observed in Bukit Tabuan and SegaraKaton Village in Karangasem, Sindu Village in Gianyar, and Bugis Village, Denpasar. The result of this study shows a similar pattern, especially how Muslim responds to their existence with adaptation, imitation and self-preservation. The use of language, following traditions and customs, and building architecture are the most frequently used media as a strategy for building dialectic communication.The acculturation of the culture has strengthened the strategy, which runs smoothly to this day, especially by the early Muslims who came to Bali, and Muslims who were soldiers and occupied tanah catu given by the king. In its relationship that lasted for hundreds of years, Hindus and Muslims also experienced dynamics. But in general, the dynamics are mostly caused by political factors and the power of economic resources, especially in the tourism sector, as well as migrants in several heterogeneous regions. Research at the four locations was carried out with a qualitative approach through interview techniques, observation and document studies.